Excellent oxygen reduction electrocatalytic activity of nanostructured CaFe2O4 particles embedded microporous Ni-Foam. (28th February 2022) - Lu, Yuzheng; Wang, Jinping; Mushtaq, Naveed; Yousaf Shah, M.A.K.; Irshad, Sultan; Rauf, Sajid; Motola, Martin; Yan, Senlin; Zhu, Bin
Abstract: Fuel cell device efficiently can convert chemical-energy (CE) of hydrogen/hydrocarbon fuels to electrical-energy. From the various types of fuel cells, solid oxide fuel cell (SOFC) unifies the advantages of combined heat and power-output with multi-fuel-flexibility. Even so, the high operating temperatures (800-1, 000 °C) leads to materials compatibility and high costs challenges. However, much progress has been made to develop low-temperature SOFCs. But poor oxygen reduction reaction (ORR) activity of traditional cathode materials at low temperatures is a key-bottleneck to reduce operating-temperature of SOFCs. Therefore, fundamental understanding of oxygen reduction reaction (ORR) is important for low-temperature solid oxide fuel cells (LT-SOFCs). Herein, we present a simple but very effective way to improve the ORR activity of an orthorhombic nanostructured CaFe2 O4 embedded on porous Ni-foam for low temperature for SOFCs cathode. The CaFe2 O4 embedded on Ni-foam exhibits a very low area-specific resistance (ASR) and excellent power output of 0.532 Wcm −2 at low operating temperature of 500 °C . The excellent ORR activity is mainly supported by the superficial release of oxygen ions with enhanced gas diffusion abilities of CaFe2 O4 by embedding on Ni-foam due to its highly porous structure. The electrical conductivity of CaFe2 O4 embedded on Ni-foam is also found to be increased dramatically. More importantly, formation of complex oxidation states (Fe 2+ /Ni 3+ and Fe 3+ /Ni 2+ ) between CaFe2 O4 and Ni-foam plays an important role on narrows the bandgap to improve the electrical conductivity and produce more oxygen vacancies to enhance the ionic transport. High electrical conductivity and electrocatalytic functionality of reported nanostructure insights new avenues for LT-SOFCs. In addition, various spectroscopies, such as UV-visible, Raman, and X-ray photoelectron spectroscopy are employed to catch the understandings of CaFe2 O4 embedded Ni-foam as new functional ORR electrocatalyst for advanced LT-SOFCs. Graphical abstract: Image 1 Highlights: Ni foam embedded CaFe2 O4 spinel ferrite is developed for LT-SOFCs cathode. Ni-foam embedded CaFe2 O4 cathode shows highly porous structure. The ORR activity of CaFe2 O4 is greatly improved by embedding it on Ni foam. The excellent electrochemical performance of the of 0.532 W cm −2 at 500 °C was achieved. It show low charge and mass transfer losses.